Analisa Penyebab Kemacetan Dan Kecelakaan Jalan Raya Ngaliyan Kota Semarang Tanjakan Silayur - Wangsa, Samba; Samba , Prasasta; Handajani, Mudjiastuti; Muldiyanto, Agus (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2021)
A traffic accident is a tragedy or accident that occurs on the road involving a motorized or heavy vehicle with other road users or without a vehicle. This incident caused the victim to suffer physical, health and material losses. Traffic accidents occur due to several factors such as human error or inadequate road conditions. Even traffic jams can also lead to traffic accidents. The problem of driving and road safety needs to be considered to reduce the number of traffic accidents that occur. This study was conducted to determine the factors that cause accidents, especially those caused by road conditions and traffic performance. The method used in the field observation research and using data on the number of accidents in 2018–2020 located on Jalan Raya Ngaliyan which was taken from the accident data of the West Semarang Police Traffic Unit. The level of road performance on Jalan Tanjakan Silayur Semarang City, at peak hours in the morning and non-peak hours during the day category C and at peak hours in the afternoon category E. Damage to the flexible pavement surface on Jalan Tanjakan Silayur is dominated by the type of damage cracks, grooves, and bleeding. One of the factors that caused the accident was because the traffic signs were not optimal on the Jalan Tanjakan Silayur section.